Directing Surface Functions by Inducing Ordered and Irregular Morphologies at Single and Two‐Tiered Length Scales. Issue 2 (18th November 2020) - Jambor, Michal; Kajánek, Daniel; Fintová, Stanislava; Bronček, Jozef; Hadzima, Branislav; Guagliano, Mario; Bagherifard, Sara
Abstract : Surface topography outlines material's interaction with its immediate environment. Herein, a series of cost‐effective and scalable treatments are used to obtain single‐scale and two‐tiered surfaces with ordered/disordered arrangements of micro and nano features. The applied treatments induced a wide variety of surface features regarding length scale and arrangement. The individual and synergistic contributions of roughness length scale, regularity, and hierarchy are analyzed on surface functionalities. The performance of further functionalized and lubricant‐infused surfaces is evaluated regarding their interaction with wetting media, as well as tribological and electrochemical resistance. The hierarchical surfaces show improved wear and corrosion resistance. The prominence of the surface features' length scale and orderedness varies based on the loading conditions and test environments. Wettability is mainly directed by micro‐scale features. Tribology is largely led by the ability of the surfaces in forming a stable low‐surface‐energy liquid interface. Electrochemical activity is primarily influenced by the synergic barrier effect of the nano‐features and the infused lubricant regardless of their arrangement. The results indicate that combining the distinctive and complementary role of micro and nano features can offer the possibility of obtaining versatile multifunctional surfaces with tunable performances based on the expected in‐service conditions. Abstract : A series scalable mechanical and chemical surface treatments are used to generate single‐scale and two‐tiered surface morphologies with ordered/disordered arrangements of micro and nano features. Multiple surface functionalities are analyzed to assess the contribution of roughness length scale and regularity as well as the extent of hierarchy to the performance of the surfaces under different conditions.